EFFECTIVENESS OF ONLINE LEARNING IN CLASS IV A SD NEGERI MERTASINGA 07 CILACAP - Suryaningsih, Ida; Pamujo, Pamujo (PROGRES PENDIDIKAN, 2021)
The COVID-19 pandemic in Indonesia affected several sectors, one of which was the education sector. With the outbreak, the government issued an online learning policy as an alternative to face-to-face learning. Online learning policies will affect the effectiveness of learning due to the lack of readiness of schools, teachers, and students. The purpose of this study was to determine the effectiveness of online learning during the pandemic. This subject were IV graders A SD Negeri Mertasinga 07Cilacap. This research type was a mixed quantitative qualitative research. Data collection techniques were obtained by observation, interviews, and questionnaires. The results of the study revealed that online learning could replace face-to-face learning during the pandemic and could run effectively if it was supported by sufficient devices and a stable internet connection as well as the teacher’s skill to use various online learning media such as WhatsApp, Google Classroom and Google Meet to attract attention and reduce student boredom.